Global agenda for livestock research: Proceedings of a consultation on setting livestock research priorities in West Asia and North Africa (WANA) region - Thomson, E.F.; Kaufmann, Ralph R. von; Li Pun, H.H.; Treacher, T.; Houten, H. van (International Livestock Research Institute, 2000)
The main purpose of this consultation was to identify research priorities and define an agenda for livestock research for development in the WANA (West Asia and North Africa) region. It was specifically intended to identify major constraints and research opportunities in relation to the roles of livestock in poverty alleviation, food security and management of natural resources, to define a regional livestock research agenda, and to identify priority topics for NARS-IARC (national agricultural research systems - international agricultural research centres) collaboration. The consultation includes presentations of papers by ILRI (International Livestock research Institute) and ICARDA (International Centre for Agricultural Research in Dry Areas) on their medium-term plans and global and regional activities; a keynote address on the role of animal foods in human diets; country presentations on major livestock related activities, production and development constraints and opportunities for research; reports from three working groups to identify research priorities for range-based and mixed crop-livestock systems, and plenary sessions to agree on the main recommendations and courses of action. The country representatives provided background information on their agricultural systems, defined the importance of different livestock components, and identified constraints to livestock production and development.